Pelatihan Bahasa Inggris Komunikatif dengan Menggunakan Metode Spying pada Siswa MANPK MAN 2 Mataram - Lela Rahmawati; Syamsurrijal, Syamsurrijal; Melati Rosanensi; Lanang Sakti (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
MANPK MAN 2 Mataram is one of the flagship madrasah programs in Indonesia. As a superior program, the education pattern is implemented using a boarding school system at State Madrasahs with the strengthening of religious and Indonesian sciences. In teaching at MANPK MAN 2 Mataram, the skills emphasized are Islamic insights but also being able to speak English communicatively and also in writing. From the results of our observations as lecturers who want to assist students at the MAN 2 PK School, we see that the problem is that these students are still lacking in mastering English vocabulary and lack of communicative English training in class, only given lots of answering practice text questions and studying grammar so that mastery of the language for speaking or communication is still lacking. To improve English speaking skills, students must also be supported by innovative methods so that maximum achievement can be achieved. In this dedication, the author uses the Spying method. By using the SPY method in this service in class, students' skills in English conversation increase. Most students actively speak and do not feel afraid and embarrassed even though they are not optimal. This method also helps them learn new vocabulary and pronunciations. Based on interviews with teachers, it can be concluded that the SPY method can help teachers increase students' interest in English subjects.